Mechanism of Stability Enhancement for Adiponitrile High Voltage Electrolyte System Referring to Addition of Fluoroethylene Carbonate - Fang, Zhao; Zheng, Zekun; Cheng, Wudan; Zhang, Xingliang; Zhong, Kenan; Li, Linbo (Frontiers in Chemistry, 2020)
To explore the high-voltage electrolyte of 5 V-level LiNi0.5Mn1.5O4 cathode material, adiponitrile (ADN) with high oxidation stability was selected as the main solvent and 2% fluoroethylene carbonate (FEC) with good film forming effect as an additive, the effect of 2 mol L-1 LiBF4-GBL/ADN+2% FEC on the electrochemical performance of LiNi0.5Mn1.5O4 was studied at room temperature. The system containing FEC additives can improve the cycle stability of the battery. At 1 C rate, the 100-cycle cycle capacity retention rate can reach 83%, while the capacity retention rate without the FEC system and the ordinary commercial electrolyte system is only 77% and 68%. Its rate performance also shows excellent performance, but the advantage of large rate performance is not obvious. In addition, by using Li4Ti5O12 as the negative electrode of the full battery, it was studied that under the synergistic effect of adiponitrile and fluoroethylene carbonate, the high-voltage electrolyte has good compatibility and lithium reversibility for the full battery.